Identification of agent associated of bacterial heart rot of pineapple (Ananas comosus var. comosus L. Merril) MD2 cultivar - Jiménez-Chinchilla, Alonso (2020)
This study aims was to identify the causal agent associated of bacterial heart rot in pineapple. Symptomatic samples were collected from pineapple plants at Agroindustrial Tres Amigos Farm, located in Piedra Alegre from Pital, San Carlos, Alajuela, Costa Rica, these samples were moved to Phytopathology and Biocontrol Laboratory from Agronomy School, Campus Technological Local San Carlos, ITCR. It was applied the classic method for to bacteria extraction, using nutrient agar as media (AN), for the bacteria identification tests was using YDC media, indolgine production, differential staining, single staining, growth evaluation at 37°C, motility, anaerobiosis, KOH at 3%, catalasa, oxidasa, gelatin hydrolysis, spores production and pectolytic activity. The symptoms seen at the field as the morphological and physiological characteristics agree with that causal agent related to this disease is Dickeya sp. (syn Erwinia chrysanthemi); on field this disease is found in a located way, but some factors as dissemination methods, optimal environmental conditions can promote a higher distribution.